2019
DOI: 10.1002/jaba.580
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different mastery criteria on the skill maintenance of children with developmental disabilities

Abstract: The acquisition of skills by individuals with developmental disabilities typically includes the attainment of a certain mastery criterion. We conducted a survey of practitioners who indicated the most commonly used mastery criterion as 80% accuracy across three consecutive sessions. Based on these results, we conducted a series of three experiments to evaluate the relation between mastery criterion and subsequent skill maintenance with 4 individuals with various developmental disabilities. Results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
73
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 16 publications
5
73
1
Order By: Relevance
“…The high levels of eye contact we observed during follow-up assessments after using the modified criteria with Logan and Natalie warrant some discussion. Richling et al (2017) evaluated response maintenance for academic tasks that children with ASD acquired using mastery criteria involving three consecutive sessions at (a) 60% or higher correct responding, (b) 80% or higher correct responding, and (c) 100% correct responding. Richling et al found that response maintenance for (a) and (b) were comparably low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high levels of eye contact we observed during follow-up assessments after using the modified criteria with Logan and Natalie warrant some discussion. Richling et al (2017) evaluated response maintenance for academic tasks that children with ASD acquired using mastery criteria involving three consecutive sessions at (a) 60% or higher correct responding, (b) 80% or higher correct responding, and (c) 100% correct responding. Richling et al found that response maintenance for (a) and (b) were comparably low.…”
Section: Discussionmentioning
confidence: 99%
“…For one participant, they used three consecutive sessions at 80% or higher as the mastery level and for the other they used five of seven sessions at 70% or higher as the mastery level. Because there is limited empirical support for specific mastery criteria (e.g., Fuller & Fienup, 2017; Richling, Williams, & Carr, 2017), we evaluated the extent to which relaxing the criteria for some participants (i.e., those who displayed variable responding) affected their performance during follow-up assessments.…”
Section: General Methodsmentioning
confidence: 99%
“…Objective statements were defined as those derived from observation rather than from inferences or opinions (Luna & Rapp, 2019). The mastery criterion was 100% of the components scored as correct for three consecutive probes during the intervention condition (Fuller & Fienup, 2018; Richling et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Additional factors for practitioners to consider in designing skill acquisition protocols are (a) a low mastery criterion (Fuller & Fienup, 2018; Richling et al, 2019) that may make it more likely that faulty stimulus control is undetected because responding under control of a noncritical feature could be considered a correct response most of the time, (b) carefully designed generalization tests to confirm the intended stimulus control, avoiding a false claim of mastery, and (c) an analysis of noncritical features when there is a failure in generalization, as these apparent failures may actually be responding under control of a noncritical feature that was consistently present during training (e.g., Rincover & Koegel, 1975).…”
Section: Discussionmentioning
confidence: 99%